RANCANG BANGUN APLIKASI WISATA KABUPATEN KUNINGAN BERBASIS ANDROID MENGGUNAKAN METODE LOCATION BASED SERVICE (LBS) - Erik Kurniadi; Heru Budianto (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2018)
Kuningan is one of the regencies in West Java which has various tourism objects. Beside nature tourism, there are also many other tourism objects such as modern water tourism that provide water boom, historical tours, religious tourism and culinary tourism. Now days the information of these tourism destination is usually through mouth to mouth, mass media, browsing¸ and social media. It makes that not all tourism objects can be visited, due to lack of information and location of scattered attractions that are difficult to reach by public transportation. This study offers an android application that can provide convenience to tourists who want to visit the tourism objects. This application provides information about the existing attractions from the start location information, facilities, opening hours and closing and guides to reach the location by using the Location Based Service method. Any travelers can download the app and run it on a smartphone. Users of the app can choose the tourism objects by category and the system will provide guide facilities to the tourist sites you want to visit. This application is expected to be a solution to the above problems and it becomes a tourism promotion media in Kuningan Regency.Keyword : Travel apss, LBS, Kuningan, Android